Jealous corona: Social media, musical propaganda and public health in Vietnam - Ó Briain, Lonán (Perfect Beat, 2021)
In March 2020, a music video produced in collaboration with the Vietnamese Ministry of Health, ‘Jealous Corona’ (Ghen Cô Vy), otherwise known as the ‘Handwashing Song’, was picked up by international media outlets including John Oliver, ABC, The Guardian and NME. The video has since received over 72 million views on YouTube, and TikTok users have posted over 33,000 personalized video responses (as of 10 February 2021). With his fieldwork plans cancelled due to restrictions on international travel, Lonán Ó Briain discusses his experience of becoming immersed into Vietnamese social media and following the TikTok phenomenon associated with ‘Jealous Corona’ online. He describes the premise behind the original production, analyses the music, lyrics and video, and then considers how young people actively engaged with the music video, became invested in its public health message and encouraged the government to rethink how musical propaganda works in contemporary Vietnam.